Klotho protein: a multifaceted regulator in aging and cancer dynamics - Sibin Nambidi; Sneha Pallatt; Antara Banerjee; Surajit Pathak; Mike K. S. Chan (Molecular Biology Reports, 2025)

A pilot study on the efficacy of a telomerase activator in regulating the proliferation of A375 skin cancer cell line - M. K. Makalakshmi; Antara Banerjee; Surajit Pathak; Sujay Paul; Neeta Raj Sharma; B. Anandan (Molecular Biology Reports, 2025)

Size dependent noble metal nanoparticles modified DNA: MD-simulation studies - Sourav Mazumdar; Ankush Chauhan; Niranjan Kumar Mridha; Narendra Nath Ghosh; Suman Adhikari; Surajit Pathak; Asoke P. Chattopadhyay; Nabajyoti Baildya (Next Research, 2025)

Fabrication of magnetite/GO/potassium copper hexacyanoferrate nanocomposite for removal of radioactive cesium ions - Isha Riyal; Krishan Kant Singh; Archana Ramola; Jyoti Rawat; Sanjay Kumar Pathak; Surajit Panja; Himani Sharma; Charu Dwivedi (Journal of Environmental Radioactivity, 2024)

A brief overview of SARS-CoV-2 infection and its management strategies: a recent update - Alakesh Das; Surajit Pathak; Madhavi Premkumar; Chitra Veena Sarpparajan; Esther Raichel Balaji; Asim K. Duttaroy; Antara Banerjee (Molecular and Cellular Biochemistry, 2024)
The COVID-19 pandemic has become a global health crisis, inflicting substantial morbidity and mortality worldwide. A diverse range of symptoms, including fever, cough, dyspnea, and fatigue, characterizes COVID-19. A cytokine surge can exacerbate the disease’s severity. This phenomenon involves an increased immune response, marked by the excessive release of inflammatory cytokines like IL-6, IL-8, TNF-α, and IFNγ, leading to tissue damage and organ dysfunction. Efforts to reduce the cytokine surge and its associated complications have garnered significant attention. Standardized management protocols have incorporated treatment strategies, with corticosteroids, chloroquine, and intravenous immunoglobulin taking the forefront. The recent therapeutic intervention has also assisted in novel strategies like repurposing existing medications and the utilization of in vitro drug screening methods to choose effective molecules against viral infections. Beyond acute management, the significance of comprehensive post-COVID-19 management strategies, like remedial measures including nutritional guidance, multidisciplinary care, and follow-up, has become increasingly evident. As the understanding of COVID-19 pathogenesis deepens, it is becoming increasingly evident that a tailored approach to therapy is imperative. This review focuses on effective treatment measures aimed at mitigating COVID-19 severity and highlights the significance of comprehensive COVID-19 management strategies that show promise in the battle against COVID-19.

Fatty Acids and their Proteins in Adipose Tissue Inflammation - Rahul Mallick; Sanjay Basak; Ranjit K. Das; Antara Banerjee; Sujay Paul; Surajit Pathak; Asim K. Duttaroy (Cell Biochemistry and Biophysics, 2024)
Chronic low-grade adipose tissue inflammation is associated with metabolic disorders. Inflammation results from the intertwined cross-talks of pro-inflammatory and anti-inflammatory pathways in the immune response of adipose tissue. In addition, adipose FABP4 levels and lipid droplet proteins are involved in systemic and tissue inflammation. Dysregulated adipocytes help infiltrate immune cells derived from bone marrow responsible for producing cytokines and chemokines. When adipose tissue expands in excess, adipocyte exhibits increased secretion of adipokines and is implicated in metabolic disturbances due to the release of free fatty acids. This review presents an emerging concept in adipose tissue fat metabolism, fatty acid handling and binding proteins, and lipid droplet proteins and their involvement in inflammatory disorders.

BMAP-27 Peptide Reduces Proliferation and Increases Apoptosis in Primary and Metastatic Colon Cancer Cell Lines - Alakesh Das; Dikshita Deka; Nabajyoti Baildya; Antara Banerjee; Atil Bisgin; Suman Adhikari; Asim K. Duttaroy; Surajit Pathak (International Journal of Peptide Research and Therapeutics, 2023)
BMAP-27 peptide is reported to possess apoptotic and anti-proliferative effects against cancer cells but the actual mechanism of action is yet to be investigated. In the current investigation, we aimed to study the role of the BMAP-27 peptide in reducing proliferation and increasing apoptosis in colon cancer cell lines. In this study, we used primary and metastatic colon cancer cell lines SW480 and SW620. Cell proliferation was measured using MTT and CCK-8 assays, and cellular damage was analyzed by lactate dehydrogenase assay. Apoptosis, cell cycle, and proliferation potentials were measured by the expression of CASPASE3, BAX, BCL-2, TP53, CDK-6, PCNA, WNT11, AXIN1 , and CTNNB1 genes. Additionally, in-silico studies were conducted to determine the binding affinities of BMAP-27 with adenomatous polyposis coli (APC) and β-catenin proteins, one of the primary regulators of colon cancer. BMAP-27 peptide reduced colon cancer cell proliferation, upregulated tumor suppressor genes CASPASE3, BAX, TP53, AXIN1 expression, and downregulated the expression of oncogenes BCL-2, CDK-6, PCNA, WNT11, CTNNB1 in both the cell lines, however, in the primary colon cancer cell line the changes are found to be more significant. The molecular dynamic simulation analysis revealed substantial binding affinity of the peptide to APC and β-catenin proteins. BMAP-27 peptide significantly inhibited the proliferation and induced apoptosis in the primary colon cancer cell line than in the metastatic colon cancer cell line. In-silico results suggest that BMAP-27 shows a strong binding affinity with APC and β-catenin proteins, highlighting its role in inhibiting colon cancer cell proliferation.

Exosomes from metastatic colon cancer cells drive the proliferation and migration of primary colon cancer through increased expression of cancer stem cell markers CD133 and DCLK1 - K. Yasodha; L. Lizha Mary; Pathak Surajit; R. Satish (Tissue and Cell, 2023)

Correction to: Wnt Signalling Inhibitors Potently Drive Trans-differentiation Potential of Mesenchymal Stem Cells Towards Neuronal Lineage - Antara Banerjee; Praveen Rowlo; Ganesan Jothimani; Asim K. Duttaroy; Surajit Pathak (Journal of Medical and Biological Engineering, 2023)

An Updated Review on Recent Advances in the Usage of Novel Therapeutic Peptides for Breast Cancer Treatment - Alakesh Das; Suman Adhikari; Dikshita Deka; Atil Bisgin; Sujay Paul; Nabajyoti Balidya; Ibrahim Boga; Antara Banerjee; Surajit Pathak (International Journal of Peptide Research and Therapeutics, 2023)

A Comprehensive Cancer-Associated MicroRNA Expression Profiling and Proteomic Analysis of Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes - Ganesan Jothimani; Surajit Pathak; Suman Dutta; Asim K. Duttaroy; Antara Banerjee (Tissue Engineering and Regenerative Medicine, 2022)
Background: The mesenchymal stem cells (MSCs) have enormous therapeutic potential owing to their multi-lineage differentiation and self-renewal properties. MSCs express growth factors, cytokines, chemokines, and non-coding regulatory RNAs with immunosuppressive, anti-tumor, and migratory properties. MSCs also release several anti-cancer molecules via extracellular vesicles, that act as pro-apoptotic/tumor suppressor factors. This study aimed to identify the stem cell-derived secretome that could exhibit anti-cancer properties through molecular profiling of cargos in MSC-derived exosomes. Methods: Human umbilical cord mesenchymal stem cells (hUCMSCs) were isolated from umbilical cord tissues and culture expanded. Subsequently, exosomes were isolated from hUCMSC conditioned medium and characterized by DLS, electron microscopy. Western blot for exosome surface marker protein CD63 expression was performed. The miRNA profiling of hUCMSCs and hUCMSC-derived exosomes was performed, followed by functional enrichment analysis. Results: The tri-lineage differentiation potential, fibroblastic morphology, and strong expression of pluripotency genes indicated that isolated fibroblasts are MSCs. The isolated extracellular vesicles were 133.8 ± 42.49 nm in diameter, monodispersed, and strongly expressed the exosome surface marker protein CD63. The miRNA expression profile and gene ontology (GO) depicted the differential expression patterns of high and less-expressed miRNAs that are crucial to be involved in the regulation of apoptosis. The LCMS/MS data and GO analysis indicate that hUCMSC secretomes are involved in several oncogenic and inflammatory signaling cascades. Conclusion: Primary human MSCs released miRNAs and growth factors via exosomes that are increasingly implicated in intercellular communications, and hUCMSC-exosomal miRNAs have a critical influence in regulating cell death and apoptosis of cancer cells. Graphical abstract

Wnt Signalling Inhibitors Potently Drive Trans-differentiation Potential of Mesenchymal Stem Cells Towards Neuronal Lineage - Antara Banerjee; Praveen Rowlo; Ganesan Jothimani; Asim K. Duttaroy; Surajit Pathak (Journal of Medical and Biological Engineering, 2022)

A review on interplay between small RNAs and oxidative stress in cancer progression - Aparimita Das; Harsha Ganesan; Sushmitha Sriramulu; Francesco Marotta; N. R. Rajesh Kanna; Antara Banerjee; Fang He; Asim K. Duttaroy; Surajit Pathak (Molecular and Cellular Biochemistry, 2021)

The impact of fusion genes on cancer stem cells and drug resistance - Saurav Panicker; Sivaramakrishnan Venkatabalasubramanian; Surajit Pathak; Satish Ramalingam (Molecular and Cellular Biochemistry, 2021)

Current insight into the functions of microRNAs in common human hair loss disorders: a mini review - Sujay Paul; Iván Licona-Vázquez; Francisco I. Serrano-Cano; Natalia Frías-Reid; Carolina Pacheco-Dorantes; Surajit Pathak; Samik Chakraborty; Aashish Srivastava (Human Cell, 2021)

Functional variations between Mesenchymal Stem Cells of different tissue origins: A comparative gene expression profiling - K. N. Sangeetha; Rosy Vennila; R. Secunda; S. Sakthivel; Surajit Pathak; S. Jeswanth; R. Surendran (Biotechnology Letters, 2020)

Wnt signaling regulates the proliferation potential and lineage commitment of human umbilical cord derived mesenchymal stem cells - Ganesan Jothimani; Rosa Di Liddo; Surajit Pathak; Monica Piccione; Sushmitha Sriramulu; Antara Banerjee (Molecular Biology Reports, 2020)

Is chronic feeding of low dose alcohol hepatotoxic or genotoxic?: A time course study in mice - Antara Banerjee; Surajit Pathak; Wen-Jian Meng; Anisur Rahman Khuda-Bukhsh (The Nucleus, 2014)

Fecal lactoferrin and intestinal permeability are effective non-invasive markers in the diagnostic work-up of chronic diarrhea - Roberta Caccaro; Renata D’Incà; Matteo Martinato; Elisabetta Dal Pont; Surajit Pathak; Anna Chiara Frigo; Giacomo Carlo Sturniolo (BioMetals, 2014)

Protective potentials of a potentized homeopathic drug, Lycopodium-30, in ameliorating azo dye induced hepatocarcinogenesis in mice - Surajit Pathak; Jayanta Kumar Das; Surjyo Jyoti Biswas; Anisur Rahman Khuda-Bukhsh (Molecular and Cellular Biochemistry, 2006)